Nigeria’s Fiscal Performance: Exploring the Role of Exchange Rate - Fagbemi, Fisayo; Olatunde, Olufemi Solomon (American Finance & Banking Review, 2020)
The paper offers empirical justifications for the instrumentality of external sector in influencing the fiscal position of a country through the exchange rate. In the study, ARDL bounds test approach to cointegration analysis is adopted to examine the long run and short run relationship between exchange rate and fiscal performance in Nigeria. The validity of the findings is based on time series data between 1981 and 2017. The emerging evidence reveals that the exchange rate movement has a substantial influence on the fiscal performance, as there exists a significant adverse relationship between exchange rate and fiscal deficit in the long run as well as in the short run, while the association between exchange rate and public debt is found to be significantly positive in both periods. Empirical elucidations posit that an appreciation of the exchange rate could lead to decreasing fiscal deficits. However, the exchange rate appreciation might not induce a reduction in public debt, as it could stimulate demand for loanable funds by the government, although such effect could be mitigated through strategic investment policy and subsidized funding schemes to aid domestic production. Given that fiscal performance is considerably driven or constrained by the exchange rate movement, the study suggests that developing a strategic framework for ensuring a realistic exchange rate and the mitigation of regular fluctuations or correcting inappropriate exchange rate is crucial.